Oleg Tamulilingan with Badung Style as the Primadona in the Performance Arts of Bali Tourism - Ni Luh Ria Novitasari; Ni Made Ruastiti; I Ketut Sariada (Randwick International of Social Science Journal, 2023)
The Oleg Tamulilingan dance is a traditional Balinese dance with the theme of romance, which depicts the romance of male and female beetles, danced in pairs by a male and female dancer. Researchers have extensively discussed the popularity of the Oleg Tamulilingan Dance. But, no one has disclosed the Badung Style in Oleg Tamulilingan Dance has remained the primadonna of the Bali tourism industry. The question is: what is the structure of the Badung version of the Oleg Tamulilingan dance?; What is the origin of the Badung-style Oleg Tamulilingan dance?. This research was conducted using qualitative methods. The data sources for this study were: Oleg Tamulilingan with Badung Style Dance, dancers, musicians, dance teachers, artists, humanists, experts, and related communities who were selected based on purposive sampling and snowball techniques. All data that has been collected through observation, interviews, and literature studies was analyzed qualitatively. The results of the research show that the Badung Style in Oleg Tamulilingan Dance is performed in the form of a loose dance depicting a male and female beetle making out in a flower garden. This can be seen from the way it is presented, the makeup and clothing, as well as the musical accompaniment used. The structures used in the Oleg Tamulilingan with Badung Style performance are pepeson, pengawak, and pengecet. The emergence of the Badung Style in Oleg Tamulilingan dance was caused by internal and external factors. The internal factor of the Oleg Tamulilingan Dance is the talent of the first dancer, Gusti Ketut Raka Astuti, who teaches his students. The external factor is the development of tourism, which provides an opportunity for the development of the Badung Style in Oleg Tamulilingan Dance and has implications for the enrichment of the presentation model of the Oleg Tamulilingan Dance.